1998
DOI: 10.1002/(sici)1097-4547(19981201)54:5<623::aid-jnr7>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Maturation-dependent apoptotic cell death of oligodendrocytes in myelin-deficient rats

Abstract: Mutations in the proteolipid protein gene (PLP/plp), which encodes the major intrinsic membrane protein in central nervous system (CNS) myelin, cause inherited dysmyelination in mammals. One of these mutants, the myelin-deficient (md) rat, has severe dysmyelination that is associated with oligodendrocyte cell death. Using the terminal deoxynucleotidyl transferase (TdT)-mediated dUTP-biotin nick end-labeling (TUNEL) assay, which labels apoptotic cells, we find that cell death is increased in multiple white matt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 66 publications
2
23
0
Order By: Relevance
“…Because the increase in proliferation of NG2ϩ cells is accompanied by an increase in the number of PDGF ␣Rϩ progenitor cells, the reduction in the number of differentiated oligodendrocytes must reflect cell death of late-stage progenitors or differentiated oligodendrocytes. This idea is consistent with morphological studies that have demonstrated that dying oligodendrocytes are more prevalent than dying progenitor cells in jp spinal cord (Skoff, 1982(Skoff, , 1995Grinspan et al, 1998).…”
Section: Discussionsupporting
confidence: 91%
“…Because the increase in proliferation of NG2ϩ cells is accompanied by an increase in the number of PDGF ␣Rϩ progenitor cells, the reduction in the number of differentiated oligodendrocytes must reflect cell death of late-stage progenitors or differentiated oligodendrocytes. This idea is consistent with morphological studies that have demonstrated that dying oligodendrocytes are more prevalent than dying progenitor cells in jp spinal cord (Skoff, 1982(Skoff, , 1995Grinspan et al, 1998).…”
Section: Discussionsupporting
confidence: 91%
“…Apoptosis in the developing brain was assessed by the terminal deoxynucleotidyl transferasemediated dUTP nick end-labeling (TUNEL) assay (Roche). TUNEL analyses were accomplished using 25 m cryosections and processed according to published protocols (Grinspan et al, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…Cell death was measured using the TUNEL analysis as previously described (Grinspan et al, 1998). To determine extent of cell death among oligodendrocyte and astrocyte populations specifically, sections were double-labeled with anti-cleaved caspase 3 (1:200, Cell Signaling) and anti-rabbit secondary antibody (1:100) and anti-PDGFRα or anti-GFAP, respectively.…”
Section: Immunohistochemistrymentioning
confidence: 99%